Tag as an Identification Marker of the Cultural Code of Society - Pandyreva, Elizaveta (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The article explores the tag as an identification marker of the cultural code of society, as well as the formation of the author's self-identification in the visual environment of the modern city. This study focused on analysing the visual series of tagging marks by studying the urban environment. The results demonstrate that tags are more than just visual elements - they perform multidimensional functions, combining street aesthetics, communication and social interaction. The study also highlights how visual symbols interact with the cultural and social aspects of urban digital spaces. The findings not only broaden the understanding of the concept of ‘tag’ but also open up new possibilities for researching its role in shaping contemporary visual art. The results of this study are of practical importance for both practitioners and scholars seeking to enrich the socio-cultural context of the contemporary visual environment.